ЗУМ-варіоптичні системи оптоелектронних датчиків - Чиж, І.Г.; Тимчик, Г.С.; Губійчук, Р.О.; Карась, О.В. (Vinnytsia National Technical University, 2026)
The main focus of this paper is on the application of adaptive optics elements in vario-optical systems of optoelectronic sensors. The aim is to provide vario-systems with variable values of their external paraxial parameters and characteristics under the condition of immobility of the system components. The basics of preliminary design of optical autofocusing systems, zoom-afocal systems and zoom-relay systems have been developed, which allow to synthesize such systems taking into account the requirements to their external characteristics and parameters. The results of studies of two-component vario-systems of these types with the use of liquid vario-lenses functioning on the effect of electro-wetting or on the use of elastomeric membrane, the shape of which is regulated by external mechanical pressure, are presented. These are the products of Corning® Varioptic®,. Optotune®. Studies of auto-focusing systems, Galileo- and Kepler-type zoom-afocal systems, and zoom-relay optical systems have shown the influence on their external paraxial parameters and on the size of their field of view of the working ranges of the optical power of vario-lenses and the diameters of their apertures. It is shown that it is possible to create zoom-optical systems of all the above-mentioned types using only two liquid vario-lenses. The influence of functional parameters of these liquid vario-lenses on the dimensions of optical systems is also shown. The materials of the article are addressed to specialists who create zoom-optical systems of optoelectronic sensors.